Flexural properties of symmetric carbon and glass fibre reinforced hybrid composite laminates - Dong, Jonathan (2020)
A study on the flexural properties of symmetric carbon and glass fibre reinforced hybrid composite laminates is presented in this paper. A modelling approach was developed with the aid of Finite Element Analysis (FEA). This model was experimentally validated. With this FEA based model, various stacking sequences were studied to find the effects of hybridisation on the flexural properties. A rule of how to arrange the carbon and glass fibres in the hybrid composite was developed. It is shown that the hybrid composite has the highest flexural strength when it contains half carbon/epoxy plies and half glass/epoxy plies. Optimisation was also carried out with the objective functions being the material cost and component weight. It is shown from the optimal hybrid composite has up to half of its plies being glass/epoxy and placed on the inside of the composite.